The research of an isolation breakdown of lights aerodrome networks - Нерет, В. І.; Сущенко, О. А. (Proceedings of National Aviation University (archive), 2021)
On the data of the normative documents and inservice experience parameter of diagnosing - isolation cable networks of aerodrome lights concerning ground is analyzed. The physical model of an insulation breakdown of these networks is investigated. The technique of definition minimum acceptable values of this parameter is offered.